Access to the Commonwealth electoral roll for medical research. Issue 2 (22nd July 2013) - Loff, Bebe; Campbell, Elissa A; Glass, Deborah C; Kelsall, Helen L; Slegers, Claudia; Zion, Deborah R; Brown, Ngaire J; Fritschi, Lin
Abstract: In the 2010–11 financial year, there was a dramatic reduction in the approvals granted by the Australian Electoral Commission for access to samples of the adult population derived from the electoral roll for the purposes of public health research. Much time and effort has been expended in making applications without success. Researchers refused access to electoral roll samples must rely on sampling methods that are not as robust and that may produce less reliable data. We outline a set of recommendations that, if adopted, will result in a fairer system for obtaining access to the electoral roll for public health research.